Land Resource Inventory (LRI) for development of sustainable agricultural land use plans using geospatial techniques: A case study of Pata Meghpar village, Jamnagar district, Gujarat - SHARMA, R. P.; SINGH, R. S.; SINGH, S. K.; ARORA, SANJAY (Journal of Soil and Water Conservation, 2018)
The soil and land resource inventory at village, as basic unit, are providing baseline data on soils, their constraints and potentials for crop production. Considering this fact, Pata Meghpar village (22013’14’’ to 22016’09’’ N latitude and 70029’16’’ to 70032’59’’ E) in Jamnagar district of Gujarat with an area of 1683 hectares was selected for land resource inventory on 1:10000 scale for land use planning activity. The soils developed on Deccan trap geological formations with distinct basaltic landforms appear at an elevation of 100 meters above mean sea level near Und river. The landform analysis of study area was carried out with the visual interpretation of Indian Remote Sensing Satellite P6 LISS-IV data of April 2012 in conjunction with cadastral map. The four basic landforms identified are isolated upland (119.3 ha & 7.1%), ravinous land (409.6 ha & 24.3%), very gently to gently sloping plains (543.9 ha & 32.3%) and nearly level plains (610 ha & 36.2%). The detailed soil survey was carried out and identified seven soil series with 10 phases. The soil series Pata Meghpar-1(Loamy, Lithic Ustorthents) and Patameghpar-2 (loamy-skeletal, Lithic Ustorthents) occurring on isolated upland are very shallow, excessively drained, brown loam (7.5YR 4/4) to dark yellowish brown (10YR 3/4), gravely loam and slightly alkaline (pH 7.2- 7.8). The Pata Meghpar-3 (fine-loamy, Typic Ustorthents) on ravinous lands are moderately shallow, excessively drained, strongly calcareous, dark yellowish brown (10YR 3/4), weak fine sub-angular blocky structure, slightly alkaline to moderately alkaline (pH 7.7 to 8.6). The Pata Meghpar - 4 (fine, Typic Haplustepts) and Pata Meghpar-5 (fine, Vertic Haplustepts) occurring on very gently to gently sloping plain are moderately deep (50-75cm), moderately well drained, slight to moderately calcareous, very dark grayish brown (10YR 3/2), moderate, medium, sub angular blocky structures and moderate to strongly alkaline (pH 8.1 to 8.8). The Pata Meghpar - 6 (fine, Leptic Haplusterts) and Pata Meghpar – 7 (fine, Typic Haplusterts) occurring on nearly level plains are deep, clayey, moderately well drained, very dark grayish brown (10YR 3/2) to very dark gray (10YR 3/1), weak fine angular blocky to moderate medium angular blocky structure, moderately calcareous and moderately alkaline (pH 8.0-8.5). The baseline resource data are useful for deriving soil-landscape relationships in basaltic terrain at village and forms the basis for upgrading management packages for sustainable crop production at farm level.